The Advent of Universal Protection of Human Rights Theo van Boven and the Transformation of the UN Role - Ramcharan, Bertrand (Springer Biographies,, 2018)
This biography tells the story of Theo van Boven's dynamic and courageous leadership to develop UN protection. Van Boven has been a life-long scholar and practitioner of human rights. He served in the Dutch Ministry of Foreign Affairs, represented The Netherlands in the UN Commission on Human Rights, served as an expert in its Sub-Commission on Human Rights, and also on the Committee on the Elimination of Racial Discrimination. He was the Director of the UN Human Rights secretariat from 1977 to 1982, and later served as Registrar of the International Criminal Tribunal for the Former Yugoslavia and for Rwanda, and as UN Special Rapporteur against Torture. As Director of the UN Human Rights secretariat, Professor van Boven built up the protection capacity of the United Nations piece by piece and thereby transformed the UN's role. He initiated every protection mechanism in use at the United Nations today. He was thus the father of the contemporary system of United Nations protection. This book is a priceless study of leadership and strategy. If one is to be able to deepen the protection capacity of the UN in the future, it is crucial to understand how the foundations were laid. This book, based on the personal papers of Professor van Boven and of the author, who was his Special Assistant, tells the story of his remarkable leadership of the UN Human Rights secretariat.